The adaptability of soybean photosynthesis to midday high-light duration through CEF-NPQ coupling regulation - Lei, Yi; Wu, Xiaoling; Gao, Jing; Wang, Qi; Wang, Jingru; Diwakar, Dhungana; Tan, Xianming; Yang, Feng; Yang, Wenyu (Frontiers in Plant Science, 2025)
Fluctuating light (FL) conditions particularly the diurnal alternation between shaded and high-light periods are intrinsic to intercropping systems and impose substantial regulatory challenges on crop photosynthesis. However, the cultivar-specific mechanisms underlying adaptation to such dynamic light environments remain largely unexplored. Here, we examined how the duration of midday high-light exposure modulates the coordination between cyclic electron flow (CEF) and non-photochemical quenching (NPQ) in two soybean cultivars grown under simulated intercropping light regimes. Plants were exposed to morning shade followed by either short (T30) or prolonged (T150, T200) midday high-light treatments. All treatments triggered common photoprotective responses, including increased energy dissipation (DIo/CSm, +18.7–22.3%) and reduced electron transport efficiency (ETo/CSm, −14.2–17.5%). Yet, the cultivars exhibited distinct photoregulatory strategies depending on light duration. The light-adapted cultivar ND12 rapidly established a proton gradient (ΔpH; 34.8% faster) and sustained higher PSII efficiency (ETRII, +41.5%) under brief high-light exposure, indicating a preemptive ΔpH priming mechanism. In contrast, the light-sensitive GX7 required extended high-light duration (T200) to induce CEF (+60.5%) and plastoquinone pool expansion (+22.0%), suggesting a delayed, duration-dependent adjustment strategy. These cultivar-specific responses ultimately enhanced photosynthetic performance by 34.8–52.4% under FL conditions. Our findings offer mechanistic insights into how midday light duration shapes genotype-dependent photosynthetic regulation, providing a physiological basis for optimizing light utilization in intercropping systems.